Correlation between production and biometric parameters in colonies of Melipona scutellaris Latreille, 1811 (Hymenoptera: Apidae) - Alves, R. M. O.; Santos, D. R.; Nascimento, A. S.; Sodré, G. S.; Carvalho, C. A. L. (Scientific Electronic Archives, 2019)
The basis of all breeding is the selection of desired features that can be sustained when the crosses are made. By identifying these parameters starts a process of linking these with the object of improvement and also between them. The aim of this study was to identify the correlation between yield and biometric of Melipona scutellaris colonies. A total of 165 colonies from consecutive generations of a crossbreeding project conducted at UFRB had the variables: number of honey pots (NPM), number of pollen pots (NPP), size of honey pots (TPM), size of pollen pots (TPP), honey production (SMEs), pollen production (PPO), colony population (POP), weight of the Queen (PRE), weight of the colony (PCO), size of the combs (ACF), number of combs (NFV), glossal size (GLO) and the area of pollen basket (COR) evaluated. The values were entered into the SAS program and calculated the Pearson’s correlations. Only four interactions presented positive values greater than 0.800: NPP x PPO (0.923), TPP x PPP (0.830), PM x NPM (0.958) and TPM x MPV (0.896). The correlations between production parameters and biometric in colonies of M. scutellaris show great variation and can be used in projects to species improve.